Digital Musical Instruments as Probes: How computation changes the mode-of-being of musical instruments. Issue 1 (April 2020) - Tahıroğlu, Koray; Magnusson, Thor; Parkinson, Adam; Garrelfs, Iris; Tanaka, Atau
Abstract : This article explores how computation opens up possibilities for new musical practices to emerge through technology design. Using the notion of the cultural probe as a lens, we consider the digital musical instrument as an experimental device that yields findings across the fields of music, sociology and acoustics. As part of an artistic-research methodology, the instrumental object as a probe is offered as a means for artists to answer questions that are often formulated outside semantic language. This article considers how computation plays an important role in the authors' personal performance practices in different ways, which reflect the changed mode-of-being of new musical instruments and our individual and collective relations with them.